Birthday stories - Murakami, Haruki (Vintage Book, 2006)
In this enviable gathering, Haruki Murakami has chosen for his party some of the very best short story writers of recent years, each with their own birthday experiences, each story a snapshot of life on a single day. Including stories by Russell Banks, Ethan Canin, Raymond Carver, David Foster Wallace, Denis Johnson, Claire Keegan, Andrea Lee, Daniel Lyons, Lewis Robinson, Lynda Sexson, Paul Theroux, William Trevor and Haruki Murakami, this anthology captures a range of emotions evoked by advancing age and the passing of time, from events fondly recalled to the impact of appalling tragedy.